Autogenesis: A Perspective on the Process of Organizing - Drazin, Robert; Sandelands, Lloyd (Organization Science, 1992)
This paper presents a perspective on organizational theory called ‘autogenesis’. This perspective has a long history in both the natural and social sciences, but is suggested particularly by recent developments in the field of self-organizing systems. According to this perspective, complex social organization can be explained in terms of the interplay of three distinct types of structure: (1) deep structure, which consists of a generative grammar (rules) for organizing; (2) elemental structure, which is the manifest form taken by individual social interactions; and (3) observed structure, which is the supra-individual group or organization as perceived by an observer of the system. The implications of this perspective for expanding the scope of theory and research on social organizations in general, and the process of organizing in particular, are discussed.